A Dyadic Approach to Understanding Associations Between Job Stress, Marital Quality, and Dyadic Coping for Dual-Career Couples in Iran - Fallahchai, Reza; Fallahi, Maryam; Randall, Ashley K. (Frontiers in Psychology, 2019)
Balancing work and family is one of the important challenges and stressors facing dual-career couples, especially for couples in Iran due to the changing sociopolitical climate. Moreover, the experience of this stress can affect partners’ martial quality. Recent studies have shown the positive impact of dyadic coping on coping with stress; however, there is a dearth of literature on understanding how supportive dyadic coping may have a positive impact on work-family stress, specifically in Iran which has a different cultural and social context compared to Western cultures wherein most research in this field has been conducted. Using a sample of 206 heterosexual dual-career couples from Iran, this study examines the associations between job stress and marital quality, and possible moderating effects of supportive dyadic coping. As predicted, job stress was negatively associated with marital quality and supportive dyadic coping moderated the association between these variables. Furthermore, we found gender differences in the associations between job stress and marital quality; women who experienced greater job stress also reported lower marital quality. The findings shed light on the possible beneficial effects of teaching supportive and common dyadic coping techniques to dual-career couples in Iran.